The management of rotator cuff tendonitis in a dancer - Armstrong, Ross (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Many forms of dance are associated with a high risk of injury due to the regular rehearsal of movements often with limited rest periods that may exceed normal range of motion and lower limb injuries are most prevalent. Aim of Study. This case study aimed to discuss the management of rotator cuff tendonitis in a dancer. Material and Methods. The patient was a female 24-year-old university dance student who attended a Sports Injury Clinic with a complaint of bilateral shoulder pain. The patient was reviewed by a physiotherapist who performed a subjective and objective assessment. Results. A diagnosis of rotator cuff tendonitis was made based upon the positive test for shoulder impingement and the reduction of these symptoms identified via a positive scapula assistance test and scapular retraction test. A positive empty can test, pain on abduction above 90° and pain on resisted abduction and tenderness were suggestive of involvement of the supraspinatus muscle. Conclusions. Management of rotator cuff tendonitis in dancers requires the identification of aggravating movements and the other underlying factors that can influence the development of this condition. A combination of pain relief, avoidance of aggravating activities and a gradual return to dance following a scapula stabilisation and rotator cuff strengthening programme proved successful.
Keywords: shoulder; injury; dance; supraspinatus; scapula stabilisation; ballet positions